Experimental and numerical analysis of residual stress in carbon-stabilized expanded austenite. (December 2018) - Peng, Yawei; Liu, Zhe; Jiang, Yong; Wang, Bo; Gong, Jianming; Somers, Marcel A.J.
Abstract: Expanded austenite obtained by gaseous carburizing of stainless steel was investigated with X-ray diffraction to determine composition-depth and residual stress-depth distributions. Avoiding ghost stress effects in the analysis of X-ray diffraction data, the obtained composition- and stress-depth profiles are in excellent quantitative agreement with those obtained with other techniques. The residual stress-depth profile was attempted calculated from the composition-depth profile assuming elastic-plastic accommodation of the lattice expansion. In the model, composition-dependence of Young's modulus, yield stress and work hardening exponent were considered. Excellent quantitative agreement was achieved between the experimental and numerical residual stress-depth profiles. Graphical abstract: Unlabelled Image